Avaliação e Gestão de desempenho em Instituições Financeiras - AGUIAR, Marlon Marques (2023)
Evaluation is an analysis process with a beginning, middle and end. Managing performance is an ongoing process that involves setting targets and monitoring results and feedback. Organizations use performance assessment and management tools in writing and using online platforms. The new market profile, characterized by technological, social and economic configurations in process in the contemporary world, has changed the face of the productive forces, with increasingly high levels of competition in organizations. The study aimed to identify how the largest financial institutions in the country perform the evaluation and performance management of their employees. As a sampling criterion, the two largest public banks, two largest private banks, the largest credit union in the country and a digital bank were defined. Interviews were conducted with six managers, documentary research was carried out with manuals, pamphlets and online material on the assessment and management of bank performance. Data collection took place from February to May, Content Analysis was used as a technique for data analysis, identifying the constituent elements of the banks' performance evaluation and management policies, via a questionnaire applied to the managers of the selected institutions. The main results obtained were in the sense that, in the selected financial institutions, there is a homogeneity by the 360 degree evaluation as an evaluation methodology. The study contributed theoretically and methodologically to the field of Performance Assessment and Management, as it presented a recurrent model, capable of replication.